The Relationship between Disciplinary Behavior and Religious Habits on the Religious Character of Students in High School - Delviany, Venny; Risnawati, Risnawati; Rizqa, Miftahir; Sabrina, Rifdah; Satrial, Ardi (International Journal of Multidisciplinary Research of Higher Education, 2024)
This research aims to analyze the relationship between disciplinary habituation and religious character, the relationship between religious habituation and religious character, and disciplinary habituation and religious habituation with religious character among high school students. This research uses a quantitative method with a correlation approach, the data source was taken using a questionnaire with a four-point Likert scale of three hundred and one respondents from a total of one thousand two hundred and twenty populations were selected using simple random sampling techniques. All data is analyzed using techniques of validation and reliability, normality, and linearity, as well as bivariate and multivariate correlation using SPPS Version 20 software. Overall the research results show that; first There is a significant positive correlation at a strong level between discipline habits and students' religious character. Second, there is a significant positive correlation at a strong level between religious habituation and students' religious character. Third, there is a significant positive correlation at a strong level between disciplinary habits and religious habits with religious character. The results of this research have proven that discipline and religious habituation are very helpful in improving students' religious character in pursuing education. These two aspects need to be the focus and attention of all groups, especially the academic community, school community, and parents.